Cross-Continental Ecological Drivers Behind Trait Clines in the Forest Grass Milium effusum - Møller, Charlotte; De Frenne, Pieter; Heberling, J. Mason; Bellemare, Jesse; Brunet, Jörg; Bruun, Hans Henrik; Cayouette, Jacques; Decocq, Guillaume; Diekmann, Martin; Frajman, Božo; Hagenblad, Jenny; Hedwall, Per-Ola; et al. (Wiley-Blackwell, 2026)
Aim
Widespread species encounter a range of variable climates that can lead to intraspecific trait clines. Such clines can be the result of phenotypic plasticity, genetic differences, or both. Although latitude often explains a large part of trait variation, it is crucial to investigate the underlying environmental variables to understand current and future trait responses. Cross-continental comparisons of species that are native on multiple continents provide a rarely used approach that can help identify the environmental drivers of intraspecific trait clines.
Location
Europe and North America.
Time Period
2021–2023.
Major Taxa Studied
Milium effusum L. (Poaceae).
Methods
To quantify the influence of environmental gradients on functional traits across geographical regions that vary in climate, we sampled M. effusum seeds from 23 European and 14 North American populations and transplanted them in a common garden. We measured 10 vegetative, reproductive, and phenological traits. We used 30-year averages of 19 bioclimatic variables, while accounting for the latitudinal and elevational position of the population origins, to compare the trait-environment relationships between continents.
Results
Our results showed that European populations occupy a broader climatic range than North American populations. Differences between continents were found in most of the traits as well as in the multivariate trait space. The traits were affected more by bioclimatic variables than by latitude or elevation. While flowering, leaf thickness, specific leaf area, and reproductive height showed parallel clines to the environment between continents, vegetative height and biomass showed contrasting clines.
Main Conclusions
Environmental influences from population origins revealed parallel clines between the continents for functional traits, suggesting shared selective pressures, while contrasting clines for plant size indicated different evolutionary trajectories, potential bottlenecks, or interactions with unknown ecological factors. This study highlights the complex interplay of genetic, environmental, and evolutionary factors in shaping phenotypic variation in native species across continents.